Padrões de diversidade beta em comunidades de girinos (Amphibia: Anura) nos Campos Sulinos - Gonçalves, Brena da Silva (2020)
Studies investigating variation between communities are useful to understand the deterministic and stochastic processes that shape the spatial and temporal communities’ distribution, mainly using approaches that assess the phylogenetic function and relationships between communities. Here, we describe and investigate the processes that generate beta diversity patterns (taxonomic, functional and phylogenetic) in anuran communities in the fields of Pampa and Mata Atlântica (Southern Grasslands). We determine which component of beta diversity (substitution and / or nesting) is associated with diversity patterns. Finally, we verify the relationship between variables of different scales on the assembly of communities in Southern Grasslands. We assessed the beta diversity metrics and identified the overriding component using dissimilarity analysis. To test the processes effects on the community, we used Mantel correlation tests between the matrices with the variables at different scales: spatial (geographical distance), biogeographic (grasslands physiognomies) and local (landscape, structural and pond complexity). Of the 160 ponds sampled, 148 (92.5%) contained tadpoles, totaling 36 species of anurans, 29 species in the Pampa and 23 species in the Atlantic Forest. We observed that the taxonomic and functional beta diversity was mainly composed by the species substitution in the Pampa and the Mata Atlântica biome. For phylogenetic beta diversity, nesting was the predominant component in both biomes. All the metrics of the Pampa beta diversity were related to the geographical distance between the ponds, to the grasslands physiognomies and four environmental descriptors (agriculture, pond area, conductivity and dissolved oxygen). All metrics of beta diversity of tadpoles found in Atlantic Forest fields were associated only with pH, while taxonomic beta diversity was related to geographical distance. We identified that there are two distinct anuran communities between the fields of Pampa and Mata Atlântica. The nesting found shows that the communities are the result of species that came from the Andes and the Mata Atlântica. However, there was diversification associated with the formation of the fields, and little dispersion due to the characteristics of the groups, generating a pattern of exchange of species and functions between / in the communities. The substitution was mainly associated with spatial and biogeographic factors, but also with deterministic factors. Thus, our work answers how the ecological processes that generated the patterns of existence of anuran species in Southern Grasslands occurred, in addition to describing the action of spatial, biogeographic and stochastic processes in the formation and maintenance of species.